Citizen participation: lessons learned from the involuntary displacement and resettlement of the Arenal Hydroelectric megaproject, Costa Rica - Avila Vargas, Gabriela (2021)
In the 1970s, there was a shortage of energy in the country and a feeling of patriotism that fostered a relationship of trust, transparency and belief in public officials and the institutions they represented, which was no exception for the people who lived in rurality, who considered being part of a megaproject that would solve the shortage of electricity in the country. The community of Arenal was investigated considering the criterion that the greater the presence of elements in livelihoods, the greater the impact, as well as the effort, on the part of the population, to recover them at the site of their involuntary resettlement; For this, primary sources and historical interviews were used. The inhabitants were in the area that would occupy the reservoir, they were the protagonists of a novel participatory process, not only because it was linked to a megaproject, but also because it was the first time that the affected population was involved and was able to take advantage of the situation. The participatory process resulted in institutional, political and legal incidence.